Air quality assessment based on R/S–SPA composite model: A case study of the Hebei province (China) - Xing, Qinfeng; Yang, Ziwei; Yao, Wanyan (Frontiers in Public Health, 2022)
Air pollution has been the favorite subject of pollution prevention and control measure with the aim of the sustainable development for ecological security. So R/S-SPA composite model is constructed to evaluate the current situation and predict the future development trend of air quality based on the data from 2013 to2020 in Hebei province. Later, the set pair analysis model was used to further verify the accuracy of the composite model. The results show that: 1) The future development trend of air quality in Hebei province will inherit the current situation, namely, gradually improve the effect; 2) The collaborative control of PM2.5 and O3 among the main pollutants is both hot and difficult, and they should be taken as the center to strengthen the joint prevention and control of other pollutants. This study deepens the understanding of air quality evaluation and the following countermeasures are formed: Adhering to the problem-oriented and goal-oriented approach to help the transformation of low-carbon development; Enhancing the awareness of energy conservation and environmental protection to practice low-carbon lifestyle; Deepening the differentiated management to lay a solid theoretical foundation for air quality.